Effect of Training Preparation for Childbirth on Fear of Normal Vaginal Delivery and Choosing the Type of Delivery Among Pregnant Women in Hamadan, Iran: A Randomized Controlled Trial - Seyedeh Zahra Masoumi; Farideh Kazemi; Khodayar Oshvandi; Mozhgan Jalali; Ali Esmaeili Vardanjani; Hossein Rafiei (Tehran University of Medical Sciences, 2016)
Objective: To examine effect of an educational program on pregnant women's fear of normal vaginal delivery. Fear of natural childbirth during pregnancy may increase the risk of caesarean section. Educational programs may be effective in reducing women fear of natural childbirth. Materials and methods: This randomized controlled trial conducted from September 2012 to January 2013 in Hamadan, Iran. One hundred fifty eligible women were randomly assigned to group "A" (Intervention group, n = 75) or group "B" (Control group, n = 75). Women in group A, participated in an antenatal educations program for physiologic childbirth in 8 two-hour sessions. A self-designed questionnaire was used to examine women's fear of natural childbirth. Data were analyzed with SPSS.16 software. Results: Baseline characteristics of women were similar in both groups. After intervention the mean fear score in group A compared to group B was significantly reduced (51.7 ± 22.4 vs. 58.7 ± 21.7) (p = 0.007). Physiologic delivery was the first choice of type of child birth after training in pregnant women in group A (58.7%). But delivery in physiologic form had lowest rate in group A (8%). Conclusion: Results of present study showed that educational program could be serving as an important tool in reducing women fear from natural childbirth and in choosing of physiologic birth. And for delivery as a physiological, education and counseling of pregnant women, doctors and midwives are required.